2019
DOI: 10.1002/joc.6339
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of stationary and nonstationary models for rainfall frequency analysis

Abstract: The development of nonstationary frequency analysis models is gaining popularity in the field of hydro‐climatology. Such models account for nonstationarities related to climate change and climate variability but at the price of added complexity. It has been debated if such models are worth developing considering the increase in uncertainty inherent to more complex models. However, the uncertainty associated to nonstationary models is rarely studied. The objective of this article is to compare the uncertainties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Traditionally, the GEV distribution assumes that observations are independent and identically distributed. However, in order to model non-stationarity in the AMR time series, many researchers allowed the parameters of the GEV distribution to change depending on the co-variate [10,22,[27][28][29]31,32,36,39]. In theory, all parameters of the GEV distribution can be applied as a function of various co-variates, but in this study, a co-variate was applied only to the scale parameter alpha, as shown below, in order to intuitively understand the effect of the co-variate.…”
Section: Non-stationary Gev Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally, the GEV distribution assumes that observations are independent and identically distributed. However, in order to model non-stationarity in the AMR time series, many researchers allowed the parameters of the GEV distribution to change depending on the co-variate [10,22,[27][28][29]31,32,36,39]. In theory, all parameters of the GEV distribution can be applied as a function of various co-variates, but in this study, a co-variate was applied only to the scale parameter alpha, as shown below, in order to intuitively understand the effect of the co-variate.…”
Section: Non-stationary Gev Distributionmentioning
confidence: 99%
“…However, the AIC (where AIC = 2 × (# of parameters) + 2 × nllh) reflecting the parsimony point of view recommends that it is more appropriate to apply the stationary model s for both AMRs of both sites. That is, as applied in Lee et al [10] and Ouarda et al [36], if an optimal model is selected using the AIC, which mainly considers the aspect of fitness of the observed AMR, the stationary model s is selected as the optimal model for the AMR at Chuncheon and Cheonan sites. The fundamental purpose of performing a frequency analysis is to estimate the rainfall quantile.…”
Section: Parameter Estimation and Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…Agilan and Umamahesh (2018) investigated the effect of covariate selection on uncertainty in the covariate-based non-stationary analysis using annual maximum series. Ouarda et al (2020) indicated that uncertainty is likely to work as a major weakness in the applicability of the non-stationary model through the analysis of UAE annual maximum rainfall series.…”
Section: Introductionmentioning
confidence: 99%